Peran media sosial dalam membentuk opini publik generasi z terhadap demokrasi di indonesia - Vardhani, Firza Amelia (Maliki Interdisciplinary Journal, 2026)
The rapid growth of social media has transformed the way Generation Z accesses information and shapes its political views, including perspectives on democracy in Indonesia. This study aims to examine the role of social media in forming Generation Z’s public opinion toward democracy in Indonesia, while identifying the challenges that arise in this process. The central problem addressed is how digital platforms such as TikTok and Instagram influence the political perceptions of young people, and the extent to which digital literacy plays a role in filtering circulating information. This study employs a descriptive qualitative approach, with data collected through in-depth interviews with university students as representatives of Generation Z, supported by observation and documentary study of relevant academic sources. Triangulation techniques were applied to ensure data validity. The findings reveal that social media significantly influences Generation Z’s political perspectives, encourages active participation, and broadens access to democratic information. However, platform algorithms also foster the formation of echo chambers and filter bubbles that limit the diversity of viewpoints. Furthermore, the widespread circulation of misinformation and hoaxes poses serious challenges to the quality of public opinion. This study concludes that strengthening digital literacy is the key solution to enable Generation Z to participate critically and responsibly in the digital democratic sphere..